English vowel sounds: Pronunciation issues and student and faculty perceptions - Garita Sánchez, María del Rosario (2019)
This article presents the results of the research project named Longitudinal Study of the Pronunciation of Vowel Sounds in English of Students from the Bachelor Degree in English Teaching at the Paraíso Campus of the University of Costa Rica. The project was conducted from 2015 to 2018, and it responded to the researchers’ concern to find out which are the most troublesome pronunciation areas for learners. The main objective of this investigation was to determine the most difficult English vowel sounds to pronounce for the learners in their first, second and third year of their major. The study also examined the students’ and professors’ perception in relation to the difficulty of these vowels sounds. As for the methodology, the study followed a correlational design within a mixed method approach that encompassed a total of 57 students divided into two groups. To gather the data, the students’ pronunciation was recorded and surveys were administered to learners and instructors. The data obtained from the recordings was processed using logistic regression; the vowels were organized from the most difficult to the easiest, and then the findings were compared to the data obtained from the surveys. The results revealed that the three most difficult vowels for students were /ɪ/, /æ/ and /ʊ/. The findings also showed discrepancies in the vowel sounds that learners and teachers perceived as difficult in comparison to the pronunciation difficulty found in the recordings. These significant differences have an impact not only on the decisions that instructors make, but also on the students’ awareness of their pronunciation problems.